2005
DOI: 10.1007/s11302-005-6311-0
|View full text |Cite
|
Sign up to set email alerts
|

P2 nucleotide receptors on C2C12 satellite cells

Abstract: In developing muscle cells environmental stimuli transmitted by purines binding to the specific receptors are crucial proliferation regulators. C2C12 myoblasts express numerous purinergic receptors representing both main classes: P2X and P2Y. Among P2Y receptors we have found the expression of P2Y 1 , P2Y 2 , P2Y 4 , P2Y 6 and P2Y 12 family members while among P2X receptors P2X 4 , P2X 5 and P2X 7 were discovered. We have been able to show that activation of those receptors is responsible for ERK class kinase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 40 publications
2
27
0
Order By: Relevance
“…Support for this hypothesis comes from in vitro studies of the mouse C2C12 cell line [43] and rat satellite cells [31]. Consistent with an in vivo role of P2X receptors during muscle regeneration, the up-regulation of several P2X receptors has been observed in muscle fibers of mdx mice [32,42].…”
Section: Discussionmentioning
confidence: 69%
“…Support for this hypothesis comes from in vitro studies of the mouse C2C12 cell line [43] and rat satellite cells [31]. Consistent with an in vivo role of P2X receptors during muscle regeneration, the up-regulation of several P2X receptors has been observed in muscle fibers of mdx mice [32,42].…”
Section: Discussionmentioning
confidence: 69%
“…Many studies have demonstrated the expression of multiple P2 receptor subtypes by skeletal muscle (Banachewicz et al, 2005;Cheung et al, 2003;Deli et al, 2007;Janssens et al, 1996); however, the pattern of purinergic receptor expression is strongly influenced by developmental stage and species (see (Burnstock et al, 2013)). …”
Section: Skeletal Muscle and Purinergic Signallingmentioning
confidence: 99%
“…For calcium measurements, cells were cultivated on 22-mm glass coverslips and, for the ethidium bromide uptake assay, in 24-well plates. Mouse satellite C2C12 myoblasts were cultured as described previously [18].…”
Section: Cell Culturesmentioning
confidence: 99%